The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.bbrc.2007.06.106
|View full text |Cite
|
Sign up to set email alerts
|

PLAGL2 translocation and SP-C promoter activity—A cellular response of lung cells to hypoxia

Abstract: Cobalt is a transition metal which can substitute for iron in the oxygen-sensitive protein and mimic hypoxia. Cobalt was known to be associated with the development of lung disease. In this study, when lung cells were exposed to hypoxia induced by CoCl 2 at a sub-lethal concentration (100 μM), their thyroid transcription factor-1 (TTF-1) expression was greatly reduced. Under this condition, SP-B promoter activity was down regulated, but SP-C promoter remained active. Therefore, we hypothesized that other facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Given that PLAGL2 can respond to environmental stress and translocate into nucleus under a CoCl 2 -induced hypoxia condition (6,8), induced PLAGL2 expression may represent a critical cellular response to outside stresses. In addition, Ubc9, a SUMO-conjugating enzyme that interacts with PLAGL2 via protein-to-protein interactions, may act as a chaperon to translocate PLAGL2 into the nucleus and activate its downstream gene activity in vivo in responding to the environmental stress (8,9). The increase of SUMOylation activity is commonly observed in cells under various stress conditions, and thus this further supports a physiological role of Ubc9 in mediating PLAGL2-programmed cellular response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that PLAGL2 can respond to environmental stress and translocate into nucleus under a CoCl 2 -induced hypoxia condition (6,8), induced PLAGL2 expression may represent a critical cellular response to outside stresses. In addition, Ubc9, a SUMO-conjugating enzyme that interacts with PLAGL2 via protein-to-protein interactions, may act as a chaperon to translocate PLAGL2 into the nucleus and activate its downstream gene activity in vivo in responding to the environmental stress (8,9). The increase of SUMOylation activity is commonly observed in cells under various stress conditions, and thus this further supports a physiological role of Ubc9 in mediating PLAGL2-programmed cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, upregulated PLAGL2 may modulate hypoxia-inducible factor-1 (HIF-1) downstream gene activity and promote HIF-1-associated cell death (17), leading to a potential pathway for PLAGL2-mediated cell death in response to hypoxia in vivo. In our previous study, we (8) showed that H441 (human lung adenocarcinoma) cells responded to CoCl 2 -induced hypoxia by accumulating PLAGL2 in the nuclei. As a transcription factor, its nuclear accumulation is likely accompanied by the regulation of its downstream genes.…”
mentioning
confidence: 98%
“…Recovered DNA from the ChIP materials was isolated using Chelex-100 (Bio-Rad Laboratories, Inc., Hercules, CA, USA). Quantitative PCR was performed with StepOnePlus realtime PCR system using a SYBR Green PCR kit and primers designed to amplify the corresponding promoter region of SFTPC [21,22]. The sequences of the primers were as follows: Forward: 5 CCGAGGGCAAGTTTGCTC 3 , and Reverse: 5 CGAAGTTTCGGTTCCCGAAC 3 .…”
Section: Chip Assay and Quantitative Pcrmentioning
confidence: 99%
“…Cobalt is a transition metal ion that can replace iron in oxygen-sensitive protein and mimic hypoxia which contributes to the development of lung disease [36]. It should be noted that CoCl 2 induces hypoxia in a sublethal concentration (100 mM).…”
Section: Discussionmentioning
confidence: 99%